Clinic-Level Factors Associated With Time to Antiretroviral Initiation and Viral Suppression in a Large, Urban Cohort. (8th November 2019) - Monroe, Anne K; Happ, Lindsey P; Rayeed, Nabil; Ma, Yan; Jaurretche, Maria J; Terzian, Arpi S; Trac, Kevin; Horberg, Michael A; Greenberg, Alan E; Castel, Amanda D
Abstract: Background: Using the results of a site assessment survey performed at clinics throughout Washington, DC, we studied the impact of clinic-level factors on antiretroviral therapy (ART) initiation and viral suppression (VS) among people living with human immunodeficiency virus (HIV; PLWH). Methods: This was a retrospective analysis from the District of Columbia (DC) Cohort, an observational, clinical cohort of PLWH from 2011–2018. We included data from PLWH not on ART and not virally suppressed at enrollment. Outcomes were ART initiation and VS (HIV RNA < 200 copies/mL). A clinic survey captured information on care delivery (eg, clinical services, adherence services, patient monitoring services) and clinic characteristics (eg, types of providers, availability of evenings/weekends sessions). Multivariate marginal Cox regression models were generated to identify those factors associated with the time to ART initiation and VS. Results: Multiple clinic-level factors were associated with ART initiation, including retention in care monitoring and medication dispensing reviews (adjusted hazard ratios [aHRs], 1.34 to 1.40; P values < .05 for both). Furthermore, multiple factors were associated with VS, including retention in HIV care monitoring, medication dispensing reviews, and the presence of a peer interventionist (aHRs, 1.35 to 1.72; P values < .05 for all). In multivariable models evaluating different combinations of clinic-level factors, enhanced adherence services (aHR, 1.37; 95% confidence interval [CI], 1.18–1.58), medication dispensing reviews (aHR, 1.22; 95% CI, 1.10–1.36), and the availability of opioid treatment (aHR, 1.26; 95% CI, 1.01–1.57) were all associated with the time to VS. Conclusions: The observed association between clinic-level factors and ART initiation/VS suggests that the presence of specific clinic services may facilitate the achievement of HIV treatment goals. Abstract : In a city-wide sample of people living with human immunodeficiency virus, certain services were associated with patients starting antiretroviral therapy and achieving viral suppression. This provides evidence for clinics in selecting services to offer to achieve optimal patient outcomes.